Pengujian Ekstrak Tumbuhan Vitex trifolia L., Acorus colomus L., dan Andropogon nardus L. terhadap Hama Pasca Panen Araecerus fasciculatus De Geer (Coleoptera: Anthribidae) pada Biji Kakao - SYLVIA SJAM; MELINA MELINA; SULAEHA THAMRIN (Jurnal Entomologi Indonesia, 2010)
Araecerus fasciculatus (Coleoptera: Anthribidae) is a primary pest mostly found in cocoa bean storage. Controlling A. fascuculatus is highly necessary, as this action would also reduce infestation of secondary pests. Utilization of natural materials as bait or trap is one applicable method to lessen damage and loss during storage. Vitex trifolia L., Acorus colomus L., and Andropogon nardus L are plant species that posess insecticidal properties that can be used to control post harvest pests. Materials used in this experiment are leaves of V. trifolia, rhizome of A. colomus and leaves of A. nardus. The three types of materials are blended and sieved with 300 mesh until finely broken up for make powder formulation. As much as 1 g of powder extract was taken then mixed with additional substract (water + CMC + saw dusts). The mixtures were then shaped in the form of ellipse resembling cocoa beans with approximately similar weight of 0.6 g (± 20 beans). Results show that V. trifolia and A. nardus are highly repellent (90.5 % and 94.5%) to A. fasciculatus, and crhizome of A. colomus is attractant to A. fasciculatus.